2018
DOI: 10.20944/preprints201803.0150.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C<sub>60</sub> Bioconjugation with Proteins: Towards a Palette of Carriers for All pH Ranges

Abstract: The high hydrophobicity of fullerenes and the resulting formation of aggregates in aqueous solutions hamper the possibility of their exploitation in many technological applications. Noncovalent bioconjugation of fullerenes with proteins is an emerging approach for their dispersion in aqueous media. Contrary to covalent functionalization, bioconjugation preserves the physicochemical properties of the carbon nanostructure. The unique photophysical and photochemical properties of fullerenes are then fully accessi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that nC 60 and its derivatives can bind to a variety of proteins (peptides) and change their conformation and structure, and the morphological characteristics of nC 60 and its derivatives have a certain effect on these bindings [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Since unmodified nC 60 is not soluble in water, most of the studies were on water-soluble nC 60 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that nC 60 and its derivatives can bind to a variety of proteins (peptides) and change their conformation and structure, and the morphological characteristics of nC 60 and its derivatives have a certain effect on these bindings [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Since unmodified nC 60 is not soluble in water, most of the studies were on water-soluble nC 60 derivatives.…”
Section: Introductionmentioning
confidence: 99%